Rational therapy of pelvic inflammatory disease - A L Tikhomirov (IP Berlin A.V., 2014)
Features of the etiology and pathogenesis of the pelvic inflammatory diseases (PID) determine the dire need for antibiotic therapy, while avoiding polypharmacy in order to improve compliance, particularly in the prescription of the empirical treatment of uncomplicated PID. The article presents data on the effectiveness of a new generation fluoroquinolone - drug Avelox® (moxifloxacin) in monotherapy genital mixed infection.